Avaliação da dinâmica e da diversidade de uma pastagem natural submetida a diferentes distúrbios - Rossi, Guilherme Ebling (2009)
Dynamics of species, families and plant functional types (PFTs), and diversity of a natural grassland submitted or not to burning and grazing, in different relief positions (concave a convex slope) were evaluated. Treatments consisted of the associations of those three factors, in a completely randomized design, with variable number of replicates, from two to five. Rotational grazing were used, with an average occupation period of six days. Grazing animals were from Nelore, Charolais and its crosses. Stocking rate was calculated to obtain between 20 to 35 % of disappearing of forage mass. Diversity was evaluated using Shannon and Simpson index and frequency of species. The analysis of dry matter availability, on the relative participation of main species and the relative frequency of the other species were performed by double sampling. Data were submitted to cluster and ordination analysis and an analysis of variance via randomization tests. With respect to diversity, burned and grazed areas had lower index than those only grazed. Considering relief and grazing interaction, higher diversity occurred in convex slope. Including burning interaction, diversity was higher in concave slope. In grazing excluded areas, higher index were observed under burning effect, and considering this factor, higher diversity were registered in convex slope. Analyzing frequency of families, Poaceae, Cyperaceae and Asteraceae were present in all plots. The most versatile species were A. lateralis, Frimbristylis diphylla and Dichanthelium sabulorum, occurring in all treatments. Burning and grazing had a positive influence in vegetation diversity, however when interacting or in its absence, they turned dynamics to a dominance of a few species. The evaluation of dynamics showed that interpretation of the results through PFTs were more efficient to explore the differences between treatments, when compared to analysis by families or by species. The seasonal dynamics of the vegetation was affected both by grazing, burning and relief position, independently if evaluated through species or functional types of plants.